3D Electrophoresis‐Assisted Lithography (3DEAL): 3D Molecular Printing to Create Functional Patterns and Anisotropic Hydrogels. (19th December 2017) - Aguilar, Juan P.; Lipka, Michal; Primo, Gastón A.; Licon‐Bernal, Edxon E.; Fernández‐Pradas, Juan M.; Yaroshchuk, Andriy; Albericio, Fernando; Mata, Alvaro
Abstract: The ability to easily generate anisotropic hydrogel environments made from functional molecules with microscale resolution is an exciting possibility for the biomaterials community. This study reports a novel 3D electrophoresis‐assisted lithography (3DEAL) platform that combines elements from proteomics, biotechnology, and microfabrication to print well‐defined 3D molecular patterns within hydrogels. The potential of the 3DEAL platform is assessed by patterning immunoglobulin G, fibronectin, and elastin within nine widely used hydrogels and characterizing pattern depth, resolution, and aspect ratio. Furthermore, the technique's versatility is demonstrated by fabricating complex patterns including parallel and perpendicular columns, curved lines, gradients of molecular composition, and patterns of multiple proteins ranging from tens of micrometers to centimeters in size and depth. The functionality of the printed molecules is assessed by culturing NIH‐3T3 cells on a fibronectin‐patterned polyacrylamide‐collagen hydrogel and selectively supporting cell growth. 3DEAL is a simple, accessible, and versatile hydrogel‐patterning platform based on controlled molecular printing that may enable the development of tunable, chemically anisotropic, and hierarchical 3D environments. Abstract : The 3D electrophoresis‐assisted lithography (3DEAL) is an affordable, tunable, and versatile fabrication process designed to print multiple types of functional molecules within different kinds of hydrogels with high precision and within large volumes. The 3DEAL platform enables chemically anisotropic environments with microscale resolution and tunable geometry.